Decline in job satisfaction and how it relates to investment decisions of the self-employed - Jörn Block; Miriam Isabell Gnad; Alexander Kritikos; Caroline Stiel (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
Despite substantial research on job satisfaction in self-employment, we know little about the specific consequences for the venture when job satisfaction declines after an external shock. Taking the COVID-19 pandemic as an example of an external shock and drawing on a sample of nearly 7,000 self-employed individuals living in Germany, we investigate how declines in job satisfaction are related to investment decisions of self-employed individuals. Having separated job satisfaction into its financial and non-financial aspects, we build in our analysis on two complementary behavioral perspectives to predict how reductions in financial and non-financial job satisfaction relate to investments in venture development. Our results show that decreasing financial job satisfaction is positively related to time investments. This finding provides support for the performance feedback perspective, where negative performance, in terms of reduced financial job satisfaction, induces higher search efforts to improve the business situation. Moreover, we also observe that reductions in non-financial job satisfaction are negatively associated with both time and monetary investments. This supports the broadening-and-build perspective in that negative experiences - in the form of reduced non-financial job satisfaction - narrow the thought-action repertoire, thus hindering resource deployment. Implications of reduced job satisfaction on investment behavior are discussed.
Keywords: L26; J28; G11; 330; job satisfaction; investment decisions; self-employment and entrepreneurship; performance feedback perspective; broadening-and-build perspective; behavioral economics; economic psychology; Germany